Anurans from the Early Miocene of Chamtwara (western Kenya), and the first fossil record for Arthroleptidae (Afrobatrachia, Ranoidea) - (:unkn) unknown (My University, 2025)
Even though anurans are present throughout eastern Africa today, their fossil record is limited to a few localities in the Oligocene and Pliocene. Here we increase knowledge about the fossil record of East African anurans by reporting on seven isolated bones from the Lower Miocene locality of Chamtwara, Kenya. Although thousands of fossils have been collected from this locality, only mammals and gastropods have been described. The frog bones are identified as belonging to an indeterminate species of Leptopelis (humerus), an indeterminate neobatrachian (humerus) and one or more indeterminate anurans (femur and tibiofibulae). The humerus assigned to Leptopelis sp. is compared to humeri from all Sub-Saharan arthroleptid and hyperoliid genera, providing the first overview of the humeral diversity of these two large afrobatrachian families. The Chamtwara Leptopelis species marks the first fossil occurrence of the Arthroleptidae and the oldest occurrence of an afrobatrachian, the fossil record of which was previously limited to the Plio-Pleistocene. This species of Leptopelis is likely closely related to Western and Central African species of Leptopelis rather than to species found in East Africa today, suggesting that by the Early Miocene the latter had already diverged from the former. This pushes the divergence between those geographical groups from the Late Miocene (~ 10 Ma) back to at least the Early Miocene (~20 Ma). Keywords Anura • East Africa • Early Miocene • Kenya • Afrobatrachia This article is a contribution to the special issue"Festschrift for Márton Venczel"
Keywords: African Research